Cooling classical many-spin systems using feedback control - Elsayed, Tarek A.; Fine, Boris V. (Physical review, 2022)
We propose a technique for polarizing and cooling finite many-body classical systems using feedback control. The technique requires the system to have one collective degree of freedom conserved by the internal dynamics. The fluctuations of other degrees of freedom are then converted into the growth of the conserved one. The proposal is validated using numerical simulations of classical spin systems in a setting representative of nuclear magnetic resonance experiments. In particular, we were able to achieve 90% polarization for a lattice of 1000 classical spins starting from an unpolarized infinite temperature state.
Gesehen am 12.12.2022